Does irrigation water applied in South Australia increase after the end of the Millennium Drought? Application of the difference-in-differences approach - Koji Noda (Water Policy, 2023)
The Millennium Drought drastically reduced the amount of irrigation water applied and triggered modern water reform, such as water market promotion in the southern Murray–Darling Basin (sMDB), Australia. South Australia (SA), located far downstream in the sMDB, occupies a unique and important position because the amount of water supplied for SA is guaranteed under normal weather conditions. The water availability for SA determines whether severe droughts occur in the sMDB. Based on the Murray–Darling Basin water market catchment dataset 2021, the causal inference of whether irrigation water applied in the SA Murray water system as the main water system in SA increased after water year (WY) 2011 when the percentage of water allocated to high-reliability water entitlements reached 100% was empirically analysed in this article with a difference-in-differences approach. In this article, the SA Murray water system was adopted as the sole treatment group and WY 2011 was selected as the treatment timing. When control variables and the interaction terms between the dummy variable for posttreatment periods and control variables are included, this article statistically demonstrates that irrigation water applied in the SA Murray water system increased after WY 2011. HIGHLIGHTS South Australia (SA) occupies a unique and important position in the southern Murray–Darling Basin as its specified water supply is guaranteed under normal weather conditions.; To evaluate the increase in irrigation water applied in SA, a difference-in-differences approach, which is a classical empirical strategy, was applied.; The SA Murray water system increased the irrigation water applied after water year 2011.;